Minor Modification in Asbestos Roof of Cow Shed for Reduction of Heat Stress in Dairy Cows during Summer Season - A.K. Mohapatra; S. K. Swain; A. K. Dash; P.S. Swain (Archives of Current Research International, 2024)
Thermo neutral zone (TNZ) is the range of ambient temperature & humidity in which animals feel comfortable and their production level is optimum. When temperature humidity index (THI) goes above 72, the dairy cows begin to show symptoms of mild heat stress, which affects the milk production in dairy animals during summer season in India. Asbestos and GI sheet are commonly used as roofing material in many cattle farms throughout the world. This experiment was carried out on apparently healthy cross bred jersey cows receiving balanced ration during the month of May in the livestock farm of OUAT, Bhubaneswar for one week. The existing cattle shed was partitioned into three compartments by raising brick walls, each having the dimension of 30 x 25 ft size. The asbestos roof of first one was covered with 90 % grade green shed-net. Over the asbestos roof of second compartment, heat reflective white colour was painted and asbestos roof of third one was left as such. From 8.00 AM to 5.00PM, the THI of the normal asbestos roof shed varied from mild to moderate heat stress range. But THI of both shed-net covered shed and heat reflective colour painted shed was found to be within the mild heat stress range i.e. 72-79 during noon indicating a comfortable ambient condition for the animals in summer season when the outside ambient temperature went up to 40 0C during noon. No significant (P>0.05) change in the milk production was observed among the groups during the week. However, a decrease (P<0.05) of 0.43, 0.25 and 0.38 L in milk yield of the cows was observed when they were kept under normal asbestos shed, heat reflective colour painted shed and shed-net covered shed, respectively. From the study, this can be concluded that the impact of heat stress on milk production can be reduced by painting the rood of the shed with heat reflective colour paint.